Estudio de factibilidad para la creación de una granja de porcinos en el recinto San Francisco de chipe del Cantón La Maná, año 2010 - Muñoz Armas, Olger Armando (2011)
Due to the quality shortage pig farms in the canton La Maná, the present research has sought to determine the profitability of a pig farm livestock built in the town San Francisco of Chipe, based in a market, technical, legal, financial and of environmental impact study. The project was based on surveys and interviews carried out with involved people in the topic. The same ones have contributed their for the design of a farm that allows the correct growth of pigs, putting in practice sanitary and nutritious condition.